Penetrating injuries in heart and in both venae cavae. A case report - Manuel Espinel González; Eduardo Dopico Reyes; Luis Martínez Arencibia (ECIMED, 2014)
We report a case of a combined wound of the heart and in the great vessels. The injury affected the right auricle and the inferior and the superior vena cava in their intrapericardiac portions. These damages were repaired by cardiorrhaphy and phleborraphy, respectively. The patient had multiple complications in the postoperative period but finally he recovered completely. Some physiopathologic aspects and of the present management of penetrating cardiac traumatisms are approached. This triple injury is not frequent and its mortality is high.